119k views
23 votes
By the distributive law 49 x 17 + 49 x 3=

User Hbin
by
4.5k points

1 Answer

5 votes

Answer:

49(17 + 3)

Explanation:

The Distributive Law says
a(b+c)=ab+ac. But it can be used in the other direction,
ab+ac=a(b+c). That way, you look at ab and ac to find the common factor a. What's playing the role of a in the expression 49 x 17 + 49 x 3? It's 49, the factor that shows up twice. That's the factor that can be taken outside the parentheses.

49 x 17 + 49 x 3 = 49(17 + 3)

User Hamed Nazaktabar
by
4.9k points